Synthesis of Carbon Dot with Citric Acid as a Base Material Using Repeated Heating in a Microwave Oven - Sujana, G. Agus Permana Putra; Sumadiyasa, Made; Isnaeni, Isnaeni (BULETIN FISIKA; Vol 22 No 1 (2021): BULETIN FISIKA February EditionDO - 10.24843/BF.2021.v22.i01.p05, 2020)
Abstrak – In this research, a carbon dot has been synthesized using citric acid and polyethylene by heating repeatedly in the microwave. The results of the synthesis were characterized by UV-Vis, FTIR, Photoluminescence (PL) and TRPL spectroscopy. The UV-Vis characterizations show that the sample has shown two peaks with the wavelength 200-280 nm and ~330 nm. This marks the  p®p * and n®p * excitation transitions which are characteristic of the carbon dot. FTIR characterization has shown the presence of O-H strain vibration bands, C=O aromatic carbonyl, C-O strain and sulfate strain vibration frequencies on wave numbers 3292, 1623, 1129 and 996 cm -1 , respectively. From the PL characterization using excitation laser beams of 320, 420 and 530 nm (violet, blue and green) obtained that the carbon dot samples produced radiation emission at wavelengths of 453, 525 and 590 nm, respectively. The TRPL calculation results show that the average lifetime of the photoluminescence is in the order of 10 -9 s, which is characteristic of fluorescence photoluminescence. These results show that a carbon dot has been successfully synthesized with radiadifferent emission characteristics depends on the laser beam.